Making successful planning applications - Haylock, Colin (London : RIBA Publishing, 2020)
How do you obtain permission? How can you satisfactorily tackle objections? How can you convince planning officers of the value of your work?Drawing on substantial experience from both applicant and local planning authority perspectives, this book provides tactics and practical steps to help architects secure early validation of applications and successful outcomes. It's a practical guide to understanding the planning system and maximizing the potential for successful outcomes. Readers will develop a greater understanding of the principles that are vital in the preparation and negotiation of applications against the very complex detail of regulatory arrangements.
OCLC-licensed vendor bibliographic record.
Keywords: Building permits -- Great Britain; Architecture, Domestic -- Great Britain -- Planning; Dwellings -- Designs and plans; Homesites -- Planning; ARCHITECTURE / Professional Practice